2015
DOI: 10.1007/s10336-015-1244-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent impact of DDT contamination on Black Stork eggs

Abstract: The contamination with DDT (1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane) and its breakdown products as a potential cause of population decline of Black Stork has been studied in Latvia since 2008. In order to test if contamination is local or widely distributed we collected failed eggs from nests also in Estonia, Belarus, Poland, Czech Republic, Germany and Belgium. DDT or its breakdown products were found in all analysed eggs. The ratio of p,p 0 -DDT as a proportion of all DDT products increased during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This may have acted in concert with climate change, particularly increased temperatures and decreased precipitation in July and August, the hottest summer months in northern Europe, when young storks fledge. Secondly, Baltic Black Storks are affected by recent DDT contamination, which has likely increased mortality among nestlings and fledglings (Strazds et al 2015). Thirdly, Black Stork nestlings and fledglings may suffer from predation.…”
Section: Discussionmentioning
confidence: 99%
“…This may have acted in concert with climate change, particularly increased temperatures and decreased precipitation in July and August, the hottest summer months in northern Europe, when young storks fledge. Secondly, Baltic Black Storks are affected by recent DDT contamination, which has likely increased mortality among nestlings and fledglings (Strazds et al 2015). Thirdly, Black Stork nestlings and fledglings may suffer from predation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unknown which processes affect the separation of the membrane in non-productive (addled) eggs. Strazds et al determined the amount of DDT in eggs [19] and found that in some, eggs membranes detached very easily in some but were inseparable in others. Camera trap and webcam data show that adult birds may accidentally squash addled eggs that have remained in the nest and discard them afterwards [13].…”
Section: B Discussionmentioning
confidence: 99%
“…Membranes are organic in nature, consisting mostly of elastin-like protein surrounded by muccopolysaccaride mantle. Conversely, eggshells are predominantly inorganic, and their organic compound, a polysaccharide complex with calcium binding properties, is distributed across the shell unevenly [19]. Thus, the organic matrix may be more prone to bonding mercury compounds.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, this relationship was poorly emphasized, perhaps due to the lack of scientific evidence regarding the white stork itself. Further contamination studies clearly showed that various stork species (Van Den Bossche et al 2002;Kamiński et al 2008;Strazds et al 2015;Orłowski et al 2019) and other farmland birds (Pinowski et al 1994;Orłowski et al 2014) are susceptible to the adverse effects of agriculturally related chemicals. Therefore, it cannot be ruled out that the contamination with DDT and its breakdown products was an important cause of the past widespread population decline of white stork in Europe.…”
Section: Population Size In 1958 and Its Long-term Variation In Polandmentioning
confidence: 99%